1999
DOI: 10.1161/01.str.30.1.40
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With Delayed Admission to Hospital and In-Hospital Delays> in Acute Stroke and TIA

Abstract: Background and Purpose-Early admission to hospital followed by correct diagnosis with minimum delay is a prerequisite for successful intervention in acute stroke. This study aimed at clarifying in detail the factors related to these delays. Methods-This was a prospective, multicenter, consecutive study that explored factors influencing the time from stroke or transient ischemic attack (TIA) onset until patient arrival at the emergency department, stroke unit, and CT laboratory. Within 3 days of hospital admiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
213
4
8

Year Published

2001
2001
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 231 publications
(244 citation statements)
references
References 41 publications
18
213
4
8
Order By: Relevance
“…Reduced knowledge and awareness of stroke is associated with delay in obtaining urgent medical attention (40,44,45), which in turn is associated with negative clinical outcomes (4,5). Inability to identify and respond to stroke could delay medical intervention and have far-reaching economic impact on the direct and indirect costs (7,46,47) seeking urgent medical attention in the instance of stroke, it is of concern that a high proportion of respondents were unable to define key symptoms of stroke.…”
Section: Discussionmentioning
confidence: 99%
“…Reduced knowledge and awareness of stroke is associated with delay in obtaining urgent medical attention (40,44,45), which in turn is associated with negative clinical outcomes (4,5). Inability to identify and respond to stroke could delay medical intervention and have far-reaching economic impact on the direct and indirect costs (7,46,47) seeking urgent medical attention in the instance of stroke, it is of concern that a high proportion of respondents were unable to define key symptoms of stroke.…”
Section: Discussionmentioning
confidence: 99%
“…Medikal talebin gecikmesindeki önemli etkenler inme semptomlarının bilinmemesi, ciddiyetinin farkına varılmaması, bunun yanı sıra hastalığın görmezden gelinmesi ve semptomların kendiliğinden düzeleceği beklentisidir (25) . Aynı zamanda yalnız yaşamak, inme olayının evde yaşanmış olması, gece saatlerinde inme görülmesi ve özellikle referans hastanelerinin acil servislerine doğrudan başvurmak yerine sağlık merkezlerine yada aile hekimlerine başvurulması en önemli geç başvuru nedenleri olarak gösterilmiştir (42) .…”
Section: Materyal Metodunclassified
“…Comparing our results with other studies, there is a divergence in delay times of admission to hospital. Some of them found time of delay 8.8 hours for ischaemic stroke , other 3 hours (11,12). In Minesota study results showed that half patients arrived within 3 hours of symptom onset, and 90% arrived within 24 hours.…”
Section: Discussionmentioning
confidence: 95%
“…Previous studies showed differencies in time of delay of admission to hospital for IS, some of them found it was 8.8 hours, other 3 hours and other more than 24 hours (11,12,13).…”
Section: Introductionmentioning
confidence: 94%